The application of lean manufacturing principles to an aircraft maintenance, repair and overhaul (MRO) company - Açıkkollu, Cihan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
This study addresses the application of lean manufacturing concepts to a non-manufacturing environment – a maintenance, repair and overhaul (MRO) company. The goal of this study is to investigate how lean manufacturing tools can be adapted for MRO work environment to identify and eliminate waste so that financial performance, productivity, quality, safety and health are improved. The study attempts to implement some of the lean techniques to an MRO company analogous to a manufacturing work environment. The idea is tested on MRO Company of Turkish Technic. First of all, value stream mapping (VSM) is used to map the current state for the C-Check maintenance package process and then used to improve the process using lean principles and map its future state. Then, 5S is used in stands and ladders area, main tool shop and seat shop to organize these worksites and eliminate unnecessary movements, and non-value-adding search, and select therbligs as well as improve safety and ergonomics issues in these work areas. Lastly, accelerated improvement workshop (AIW) is used as the tool to improve the assembly process of HPC Forward and HPT Shroud / LPT Nozzle modules of an aircraft engine. Results of the study showed that VSM indicated the waste and bottleneck areas in the C-Check package process. It also provided an implementation plan, which reduced the lead time of a package from 12 days to 2½ days. In addition, 5S provided an efficient and organized workplace and eliminated safety and ergonomics problems related with the work area. Finally, AIWs helped to increase efficiency significantly for three module assembly processes. All these improvements showed that lean manufacturing methods can be applied in an MRO company in order to increase productivity by eliminating waste.
Keywords: Manufacturing processes.; Airplanes -- Maintenance and repair.